P091 PHYSICIANS INCONSISTENTLY MONITOR VITAMIN D IN INFLAMMATORY BOWEL DISEASE PATIENTS: GENDER AND ETHNICITY MAY PLAY A ROLE. (18th January 2018) - Dodds, Kerian; Dave, Jenny; Almedimigh, Abdulaziz; Al-Abbas, Bedoor; Alsulaimi, Najwan; Rowe, Anthony; Fairfield, Bradley; Chandler, Matthew; Myint, Aung; Borum, Marie L
Abstract: Vitamin D may have a role in immune regulation and be associated with inflammatory bowel disease (IBD) expression. IBD patients are more likely to be vitamin D deficient than the general population. However, it is uncertain if vitamin D monitoring in IBD is consistently performed. This study evaluated the frequency of vitamin D testing in IBD patients at a university gastroenterology practice. A chart review of consecutive IBD patients during a 6 month period was performed. Patient age, gender, ethnicity were obtained. Vitamin D levels within the past year were noted. In vitamin D deficient (<30 ng/ml) patients, the frequency of supplementation was assessed. Database was created maintaining patient confidentiality. Analysis was performed using Fisher Exact test (significance set at p<0.05). This study was approved by the IRB. Records of 268 patients (118 men, 150 women; mean age 43) were evaluated, with 158 Crohn's, 109 ulcerative colitis and 1 indeterminate colitis. 207 (77.24%) had vitamin D levels. There was a significant difference (p=0.049) of vitamin D testing in women (122/150; 81.33%) and men (85/118; 72.03%). In the 138 (66.67%) vitamin D deficient patients, whites (61; 79.49%) were more often deficient (p=0.003) than nonwhites (63/60.78%). 64 of 138 (45.6%) vitamin D deficient patients received supplementation, with no difference based upon gender (p=0.864) or ethnicity (p=1.000). While vitamin D may have a role in IBD, there are limited studies evaluating whether physicians obtain vitamin D levels. This study revealed inconsistent vitamin D monitoring and infrequent supplementation in deficient patients. Notably, women were more often tested than men and whites were more often deficient than non-whites. This study is limited based upon reliance upon documentation and single institution design, but it offers a foundation for future research. Increased efforts are needed to ensure consistency in vitamin D testing in all patients to optimize management.